Gingipains, the major cysteine proteinases and virulence factors of Porphyromonas gingivalis: structure, function and assembly of multidomain protein complexes - Potempa, Jan; Sroka, Aneta; Imamura, Takahisa; Travis, James (Current protein & peptide science, 2003)
Gingipains, extracellular cysteine proteinases of Porphyromonas gingivalis, constitute the major virulence factor of this periodontopathogenic bacterium. They are the product of three genes, two coding for an Arg-specific (RgpA and RgpB) and one for a Lys-specific proteinase (Kgp). Proteinase domains of RgpA and RgpB are virtually identical; however, the gene encoding the former enzyme is missing a large segment coding for hemaglutinin / adhesin (HA) domains. The latter domains are present also in Kgp. The tertiary structure of RgpB revealed that the proteinase domain of gingipains has a protein fold referred to as the caspase-hemoglobinase fold. On this basis, they are also evolutionary related to other highly specific proteinases including clostripain, caspases, legumains and separase (clan CD of cysteine peptidases). Gingipains are produced as large preproproteins and are subject to elaborate, not yet fully understood, secretion, glycosylation, activation, and maturation processes. How they traverse the outer membrane is unknown, although it can be hypothesized that they use an autotransporter pathway. Apparently during transport through the periplasm the LPS-like glycan moiety is added at the conserved C-terminal portion of progingipains. At the cell surface pro-gingipains fold into partially active, single-chain zymogens and undergo autocatalytic, intermolecular processing. Two sequential cleavages within the profragment domain enhance zymogen activity and in the case of RgpA and Kgp are followed by excision of the individual HA domains. These domains are further truncated at the C-terminus by concerted action of Kgp and carboxypeptidase and form a non-covalent multidomain, multifunctional complex anchored into the outer membrane by the glycated, C-terminal HA domain. This hypothetical scenario is a reasonable explanation for the occurrence of many forms of gingipains.